Bringing the workplace to its most desirable state for the employees despite COVID - Tamesis, Chris C. (Animo Repository, 2021)
The growing stress of employees because of the changes in social interaction and the government-required COVID-related protocols that need to be followed in the workplace has significantly affected the efficiency of the employees which hampered the growth of companies. The foremost explanation for this is the inability of the companies to adjust to the changing environment. The preceding set of principles regarding the happiness and engagement of employees has been made without consideration of a worldwide pandemic. Thus, this paper aims to have an analysis of the workplace concerning the employees’ happiness despite COVID, to arrive at recommendations for proper adjustments that need to be done due to the additional stress that the pandemic has been causing. In addition to the previously set principles of employee engagement, it is proven by this research that the employees need holistic support by having the (a) proper facilities; (b) right culture; and (c) proper personal growth for employees, to alleviate the employees from the drowning feeling of stress from covid.